Experiences and outcomes from a traveling innovation lab experiment. Issue 2 (31st May 2019) - Saegebrecht, Florian; John, Christian; Schmiedgen, Peter; Noennig, Jörg Rainer
Abstract : Purpose: The purpose of this paper is a case study evaluation based on a mobile innovation lab experiment – a new training and service format that offers innovation trainings on a mobile basis for schools in rural regions. Design/methodology/approach: The research aims to connect concepts of "entrepreneurial orientation and education" and "innovation adoption." The objective of the case study is to test the readiness of pupils and schools for the provided innovation trainings and services to increase innovation capacities. Findings: The case study is based on an explorative survey of 778 pupils at 18 schools and shows an increased awareness of innovative thinking and entrepreneurial capabilities. Research limitations/implications: The findings and implications are not generalizable owing to predefined project region and the prototype character. The study offers basic insights into the specific processes and determining factors and mechanisms of innovation promotion in limited spatial work forms. Practical implications: A mobile innovation environment focused on trainings and modern technologies was created. The workshops strengthened the entrepreneurial intention and potential of pupils to foster long-lasting innovation potential in the region. Social implications: The tested concept improves the method-based development of creative project ideas, thereby strengthening the regional cohesion and the economic perspective in the project region. Originality/value: After extensive research, the authors assume there is no comparable concept offering entrepreneurship education and latest technologies in a mobile innovation environment, at the time of submitting this paper.